Environmental chromium from the tannery industry induces altered reproductive endpoints in the wild female small Indian mongoose (Urva auropunctatus). (February 2019) - Andleeb, Shaista; Mahmood, Tariq; Khalid, Azeem
The populations of wild animals are declining in many parts of the world in response to man-made alterations in the environment. Environmental contamination due to heavy metals discharge from industry may contribute to the decline of wild animal populations by impacting their reproduction, growth, and development. In the leather tanning industry, chromium (Cr) is used as a basic component, but it is a potent toxicant that can affect many of the physiological functions of animals. In the current study, we investigated the reproductive toxicity of industrial Cr in female small Indian mongooses inhabiting a tannery area. Adult female specimens were live trapped from February 2015 to January 2016. Blood and other body tissues (ovaries, kidneys and liver) of the captured specimens were collected along with soil and water samples from the environment for analysis. The Cr concentrations were found significantly ( p < 0.0001) increased compared to control in the environment, blood, and all body tissues of the animals. Estradiol and progesterone levels were found to be significantly decreased in comparison with control ( p < 0.0001), along with reduced ovarian weights, while follicle stimulating hormone (FSH) and luteinizing hormone levels were found significantly ( p < 0.0001) elevated. Light microscopy revealed significantly decreased in comparison with control ovarian follicle numbers ( p < 0.0001) and diameters, vacuolization of the oocytes, and a significantly higher percentage of atretic follicles inside the ovary. We conclude that Cr discharged from the tanneries is absorbed by the exposed female small Indian mongoose, leading to ovarian dysfunction with potential impairment of reproductive function.